The Awareness of Lean Tools Applying in Thai Logistics SMEs - Janyapoon, Suwat; Tunyaplin, Suratin (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This study focuses on analyzing the level of awareness and the adoption of lean tools in small and medium-sized enterprises (SMEs) in Thailand within the field of logistics management, which is a key factor influencing organizational efficiency and cost reduction. A random sample of 42 SMEs in the logistics sector was conducted using in-depth interviews and questionnaires to measure the level of awareness regarding lean tools. The relationships between variables were analyzed using Pearson’s Correlation statistics. The research encompasses a survey of essential lean tools, including 5S, Kanban, Kaizen, and Visual Management, aiming to establish sustainable operational standards. The findings reveal that SMEs with higher registered capital tend to have a greater awareness and application of lean tools than those with lower capital. However, lean implementation in SMEs generally lacks consistency and aims to address immediate issues. There is also a lack of systematic embedding of lean principles across all employee levels, limiting lean practices’ full benefits. This study recommends that SMEs develop lean skills suited to their specific context and constraints. It also emphasizes the need for increased managerial support in implementing lean concepts to reduce costs and enhance long-term competitiveness.